RESIDU BAHAN AKTIF ASAP OBAT NYAMUK BAKAR YANG TERBUAT DARI DAUN LEGUNDI (Vitex trifolia L.) PADA ORGAN PARU-PARU MENCIT - Sri Wahjuni (DiscoverSys Inc., 2014)
Research of analysis of active ingredient residues of mosquito coil smoke made of leaves legundi (Vitex trifolia L.) in the lungs of mice by gas chromatography-mass spectroscopy (GC-MS) was carried out. Mosquito coil made from the leaves legundi (Vitex trifolia L.) was burned and the smoke is exposed to male mice (Mus muculus) for 20 days (acute exposure). Mice that had been exposed to mosquito coil smoke legundi (Vitex trifolia L.) anesthetized with cotton that has been moistened with chlorofom solution, then mice were dissected and their abdominal organs was taken transversely to the lungs. Lungs of mice was macerated with ethanol 96% for 1x24 hours. Then extracted lungs of mice were analyzed by GC-MS. A number of 15 compounds from legundi (Vitex trifolia L.) mosquito coil smoke were identified using GC-MS, including: methenamine; 2-methoxy-4-vinylphenol; 2, 6-dimethoxyphenol; 4-hydroxy-3- methoxy-benzoic acid; 2-methoxy-4-(1-propenyl) phenol-E; 5-tert-butylpyrogallol, 1, 3, 7, 7-tetra methylbicycloheptan-2-one, 2, 3, 5, 6-tetrafluoroanisol; diethyl pthalate, 2, 6 - dimethoxy-4-(2-propenyl) phenol; N-N-dimethyl methanesulfonamide; 4-hydroxy-3-nitrocoumarin; citenamide; 1- methyl-anthraquinone; and hexamethyilcyclotrisiloxane. Lungs of mice analyzed using GC-MS found a compound of hexamethyilcyclotrisiloxane which was similar to compound observed in legundi (Vitex trifolia L.) mosquito coil smoke.